2023
DOI: 10.33448/rsd-v12i3.40551
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de uma formulação semissólida à base de epiisopiloturina e avaliação da sua estabilidade

Abstract: A mucosite oral é um efeito colateral comum associados as modalidades terapêuticas para o câncer. Esse trabalho tem por objetivo desenvolver uma formulação semissólida utilizando epiisopiloturina (EPI) como princípio ativo, avaliando a estabilidade e seu perfil de liberação in vitro. A EPI foi combinada com os excipientes: carbopol, metilparabeno, glicerina, trietanolmaina, água, vaselina, lanolina e mentol. Para avaliação físico-química foram realizados os testes de centrifugação, pH, ciclo gelo-degelo e cara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Ethmoidal arteries, which originate in the ophthalmic and internal carotid arteries, provide an abundant blood supply to the nose [8]. Substances can enter the central nervous system via the perivascular areas surrounding these arteries [5,11].Studies comparing intranasal and arterial administration in animals have shown that substances administered in the former route enter the cerebral perivascular spaces within 20 minutes [16], are found in greater concentrations in the dura mater and circle of Willis [17], and are found in greater concentrations in the deep and superficial cervical nodes of rats [95], indicating that they may be transported via lymphatic drainage from the nasal passages and CSF. The maxillary, ophthalmic, and facial arteries, all of which are branches of the carotid artery, are the primary routes through which intranasal medicines reach the central nervous system.…”
Section: Intranasal Administration As An Alternative To the Oral Rout...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ethmoidal arteries, which originate in the ophthalmic and internal carotid arteries, provide an abundant blood supply to the nose [8]. Substances can enter the central nervous system via the perivascular areas surrounding these arteries [5,11].Studies comparing intranasal and arterial administration in animals have shown that substances administered in the former route enter the cerebral perivascular spaces within 20 minutes [16], are found in greater concentrations in the dura mater and circle of Willis [17], and are found in greater concentrations in the deep and superficial cervical nodes of rats [95], indicating that they may be transported via lymphatic drainage from the nasal passages and CSF. The maxillary, ophthalmic, and facial arteries, all of which are branches of the carotid artery, are the primary routes through which intranasal medicines reach the central nervous system.…”
Section: Intranasal Administration As An Alternative To the Oral Rout...mentioning
confidence: 99%
“…More research into SEDDS technology [14] has been prompted by the commercialization of drugs like SandimmunNeoral®, (cyclosporin A) by Novartis Pharmaceuticals (USA), Norvir® by AbbVie Inc. (North Chicago, IL, USA), and Fortovase® by Roche (Basel, Switzerland). [15,16] In addition to these, there are currently on the market products that are based on liquid SEDDS that are either encapsulated in hard gelatin capsules (Gengraf® (cyclosporine) (AbbVie Inc., North Chicago, IL, USA) or in soft gelatin capsules (Agenerase® (amprenavir) (Glaxo Group, United Kingdom), Depakene® (valproic acid) (AbbVie Inc., North Chicago, [17,18]. It's true that SEDDS might be expanded to include most medications from BCS's classes II and IV.…”
Section: Introductionmentioning
confidence: 99%
“…Ademais, os valores de pH das formulações oscilaram em torno de 5,0 a 5,5, visto que, essa variação ocorreu formulação 2, em seu 2° ciclo de estresse térmico, possivelmente por reações químicas como hidrólise, impurezas, decomposição e/ou armazenamento inadequado [21]. Em síntese, os aspectos faciais são subdivididos em camadas, onde no estrato córneo apresenta um pH de 5,5, sendo ele, o primeiro a ser exposto a contato com produtos cosméticos.…”
Section: Determinação De Ph E Densidadeunclassified
“…Sendo assim, realizar o teste de pH é relevante e necessário para assegurar a estabilidade e eficácia de uma formulação. O pH do gel se manteve aceitável de acordo com a faixa indicada, sendo um fator importante para os testes da formulação analisada, pois pH baixo pode causar irritação, sensibilidade e alergia, entre outros fatores (Souza, 2020;Carneiro et al, 2023;Cavalcante et al, 2022).…”
Section: Determinação Do Phunclassified